If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y-3=2y+12
We move all terms to the left:
y-3-(2y+12)=0
We get rid of parentheses
y-2y-12-3=0
We add all the numbers together, and all the variables
-1y-15=0
We move all terms containing y to the left, all other terms to the right
-y=15
y=15/-1
y=-15
| 6(2y)-4=0 | | 12-10h=-108 | | 3/4(1/4x+8)-(1/2+2)=3/8(1/4)-1/4 | | (6x+6)(5x+8)=0 | | 5|x-2|=20 | | -231=4x-7(-6x-13) | | 3(p+4)=2(p-18) | | 8(w-4=5w-50 | | 2x-4(-3x-18)=-40 | | 2(x+3)+5x=3(2x-2) | | -3a=-(a- | | 9b-8+4b=7b+16 | | y=19,000(9^-0.07*5) | | 30=2x+5(x+13) | | 178=-3x+4(-6x+4 | | 10y−6=5y+9 | | -72=-6x-3(-5x+9) | | x2+12x+15=75 | | 1.8(5x+3)+5.6=29 | | 97^-3=x | | -240=7x-4(-4x+14) | | 9-4a=-15 | | 9y^=-9999999999 | | 3.5+x=90 | | 7x-3=5x= | | 7x-6(x-7=53 | | -3x-6(4x-5)=-186 | | 85=23^x | | 3x-5=2+x | | 32=4x-2(6x+8) | | 12x-1+4x+2+9x–13=180 | | 9x+3=4x+16 |